2011
DOI: 10.5586/asbp.2005.017
|View full text |Cite
|
Sign up to set email alerts
|

Do small-scale gaps in calcareous grassland swards facilitate seedling establishment?

Abstract: In this study we analyzed gaps originated in different seasons of the year vs. places of close vegetation in calcareous grasslands in terms of their suitability for seedling germination and establishment. Gaps, irrespective of the time of their origin, significantly promoted seedling emergence as compared with close swards. However, the season of gap creation influenced the rate of seedling germination/emergence. Seedlings occurred more frequently in autumn and spring gaps than in the summer ones. The highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Experiments in Western Europe and in the area studied have shown that although grazing or mowing is enough to keep this species at low density (Bąba, 2003(Bąba, , 2004Bobbink and Willems, 1987;Farmer and Baxter, 1998) the restoration of species diversity of calcareous grasslands depends mainly on the local species pool (Koch et al, 2011;Pärtel and Zobel, 1999) and on the soil seed bank, which is usually poor under a dense sward of B. pinnatum (Bąba and Kompała-Bąba, 2005;Stampfli and Zeiter, 1999). Besides measures to limit the dominance of B. pinnatum, success in restoring calcareous grasslands from monodominant stands depends on sowing local ecotypes of calcareous grassland species to enrich the local flora (Pywell et al, 2002).…”
Section: Conclusion and Implications For Managementmentioning
confidence: 98%
See 1 more Smart Citation
“…Experiments in Western Europe and in the area studied have shown that although grazing or mowing is enough to keep this species at low density (Bąba, 2003(Bąba, , 2004Bobbink and Willems, 1987;Farmer and Baxter, 1998) the restoration of species diversity of calcareous grasslands depends mainly on the local species pool (Koch et al, 2011;Pärtel and Zobel, 1999) and on the soil seed bank, which is usually poor under a dense sward of B. pinnatum (Bąba and Kompała-Bąba, 2005;Stampfli and Zeiter, 1999). Besides measures to limit the dominance of B. pinnatum, success in restoring calcareous grasslands from monodominant stands depends on sowing local ecotypes of calcareous grassland species to enrich the local flora (Pywell et al, 2002).…”
Section: Conclusion and Implications For Managementmentioning
confidence: 98%
“…This region has a system of deep Upper Jurassic limestone valleys and limestone hills spread across an agricultural landscape, with fields and fallows on the plateaus between them. B. pinnatum occurs in most of the old and recent calcareous grasslands, often forming dense, nearly monodominant stands (Bąba, 2004;Bąba and Kompała-Bąba, 2005;Czarnecka, 2004).…”
Section: Study Area and Sampling Schemementioning
confidence: 99%
“…Additionally, the herb layer is more compacted compared to the herb layer from plot A. In plot B, there were no gaps which contributed to the recruitment and recovery of numerous grassland species because of better light conditions [40,41]. Lack of gaps and more compacted herb layer influences the structure of Pulsatilla patens-on overgrowing grassland, no juvenile individuals occurred; the total abundance of species was 5 times lower, compared with open grassland; in distribution type, no clusters were noted, and the leaf rosettes were smaller than in the open xerothermic grassland (Figure 1).…”
Section: Discussionmentioning
confidence: 96%
“…It is worth mentioning that such openings in continuous turf are considered as safe sites for seedling recruitment sensu Harper [65], regeneration niche sensu Grubb [66] and space "free from competition" [67]. The beneficial role of small-scale gaps enabling spontaneous recruitment and establishment of seedlings in calcareous grasslands was repeatedly proved in naturally originated [68], as well as experimentally made openings [69,70]. In the present study, the recorded greater mean cover-abundance degree of a species along the narrow pathways than along the wide ones might suggest the successful generative propagation and/or undisturbed vegetative spread, leading to the multiplication of individuals and/or ramet number, as well as an area of individuals presumably owing to the non-intensive use of trails by visitors.…”
Section: The Plant Cover Characteristicsmentioning
confidence: 99%